IMPROVING THE ABILITY OF MATHEMATIC CONNECTION AND SELF-CONFIDENCE’S STUDENT OF JUNIOR HIGH SCHOOL THROUGH PROBLEM-BASED LEARNING - Ade Nur; Euis Eti Rohaeti; Rippi Maya (IKIP Siliwangi, 2018)
This study aims to examine the achievement and improvement of the ability of mathematical connections and confidence of students through problem-based learning model. The population in this study is all students of 7th grade from one of SMP Negeri in Bandung. Samples were taken at random class. Among the eleven classes, two classes were selected as an experimental class (VII-K) and a control class (VII-B). The research instruments consist of a test instruments (math connection ability) and a non-test instruments. The instrument in the form of test is a set of test questions to measure students' mathematical connection ability. While non-test instruments in the form of a scale of students' self-confidence, and the scale of student opinions on problem-based learning. Research shows that the achievement and improvement of the ability of mathematical connections and confidence of students whose learning using problem-based learning model there is a difference with the learning using ordinary learning in terms of the initial ability level of students. There is no interaction between the problem-based learning model and the student's initial ability level to generate mathematical connections and students' self-confidence. In addition there is a correlation between the ability of mathematical connections and students' self confidence in the classroom that uses the problem-based learning model as well as in the classroom using ordinary learning.